The Role of the Local Champion in the Development of Wanurejo Tourism Village - Prakoso, Aditha Agung (Journal of Tourism and Creativity, 2024)
Wanurejo Village is one of 20 villages in Borobudur Subdistrict that was developed into a tourist village to support the development of temple tourism that has developed previously with the existence of Borobudur, Mendhut, and Pawon Temples around the village area. The existence of this tourist village, which was pioneered in 1999, has made a major contribution, both in terms of economic and regional development, to the community and, of course, to the village itself. This is due to the movement of local champions who became initiators in the development of tourism activities in Wanurejo. This study aims to explain the role of local activists in the development of Wanurejo Tourism Village using a qualitative descriptive method based on a stage of rural transformation approach, so that this study can find a timeline that explains in detail the role of local champions at each stage.